Philadelphia : a chronological & documentary history, 1615-1970 - Siegel, Adrienne (Dobbs Ferry, N.Y. : Oceana Publications, 1975)
A chronology of important events and people in Philadelphia accompanied by pertinent documents.
Includes index.
Bibliography: p. 135-152.
Keywords: Philadelphia (Pa.) -- History -- Chronology; Philadelphia (Pa.) -- History -- Sources; Philadelphia (Pa.) -- History